CSB investigation of Chevron Richmond refinery pipe rupture and fire. Issue 4 (14th September 2015) - Grim, Lauren; Tillema, Dan; Cutchen, Steve; Wingard, Mark; Johnson, Amanda
Abstract : The U.S. Chemical Safety and Hazard Investigation Board (CSB) investigated a pipe rupture of a high temperature light gas oil line at the Chevron Richmond Refinery in Richmond, CA. The CSB found technical, regulatory, and Chevron organizational factors causal to the incident. This article is a summary of the technical and organizational analysis presented in the CSB final investigation report on the Chevron Richmond Refinery incident. © 2015 American Institute of Chemical Engineers Process Saf Prog 34: 355–359, 2015